The pageant of American history - Leinwand, Gerald (Boston : Allyn and Bacon, 1975)
A textbook outlining the history of the United States emphasizing its role as an urban nation of immigrants and migrants.
Includes bibliographies and index.
Keywords: United States -- History; United States -- History